The effects of vildagliptin on glycemic variability in patients with type 2 diabetes on premixed insulin therapy - Kong, Deyue; Shen, Ziyang; Jiang, Lanlan; Xie, Xiaojing; Yan, Rengna; Jing, Ting; Hu, Yun; Ma, Jianhua (Frontiers in Endocrinology, 2025)
AimPatients on premixed insulin therapy usually have poor glycemic control. This study aimed to investigate the effect of vildagliptin in these patients.MethodsThis real-world study included patients with type 2 diabetes mellitus (T2DM), who were poorly glycemic controlled on premixed insulin therapy and were subsequently added vildagliptin. The control group consisted of patients who only had their insulin doses adjusted without adding vildagliptin, matched for age, diabetic duration, HbA1c, and BMI. All patients underwent FGM, glycated hemoglobin(HbA1c), and glycated albumin(GA) measurements at baseline and three months after the treatment adjustment.ResultsPatients receiving vildagliptin treatment demonstrated significant reductions in HbA1c and GA levels (P<0.001 and P=0.009, respectively). The vildagliptin group exhibited a remarkable decrease in the mean amplitude of glycemic excursion (MAGE) (8.58 ± 0.36 vs. 6.62 ± 0.47, P<0.001), along with notable reductions in mean blood glucose (MBG) (10.7 ± 0.34 vs. 8.82 ± 0.39, P<0.001) and time above the target range (TAR) (52.60 ± 3.44 vs. 31.59 ± 4.31, P<0.001) compared to the control group. Moreover, there were notable improvements in the duration spent within the target range (TIR) (45.64 ± 3.33 vs. 64.22 ± 4.00, P<0.001), along with increases in the areas under the curve (AUC) for blood glucose levels above 4.4 (426.82 ± 83.19 vs. 892.16 ± 185.27, P=0.018) and 3.9 (213.81 ± 47.20 vs. 454.77 ± 103.21, P=0.029). Hourly mean blood glucose levels over a 2-week period monitored by FGM indicated lower blood glucose levels in the vildagliptin group, particularly after dinner (P=0.022).ConclusionVildagliptin added to premixed insulin effectively lowers blood glucose levels and reduces glycemic variability in patients with type 2 diabetes mellitus.Clinical Trial Registrationhttps://clinicaltrials.gov, identifier NCT04847219.